Anti-inflammatory effects of vinpocetine in LPS-stimulated microglia via activation of AMPK - ZHOU,QIN (2020)
Abstract Microglia are the resident immune cells in the central nervous system (CNS), which play important roles in the repair of neuroinflammatory injury. The present study investigated the anti-neuroinflammatory effects of vinpocetine induced by lipopolysaccharide (LPS) in BV2 microglia. BV2 microglia were pretreated with vinpocetine, and then stimulated with LPS (100 ng/mL). The cytotoxicity of BV2 microglia was assessed by MTT assay. The expression levels of nitrite oxide were measured by Griess assay. Proinflammatory cytokines and mediators were determined by Western blot, ELISA, or quantitative real-time PCR. Vinpocetine significantly decreased the generation of nitric oxide-inducible nitric oxide synthase (iNOS), cyclooxygenase- (COX-) 2 in a dose-dependent manner. In addition, vinpocetine decreased the production of pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α), interleukin (IL)-6 and IL-1β. Furthermore, it was observed that phosphorylation levels of AMPK (Thr-172) decreased in LPS-stimulated BV2 microglia. Vinpocetine treatment increased AMPK phosphorylation in LPS-stimulated BV2 microglia. AMPK inhibition by siRNA blocked the anti-inflammatory effects of vinpocetine induced by LPS in BV2 microglia. The overall results demonstrate that vinpocetine has anti-inflammatory effects on LPS-stimulated BV2 microglia via inducing phosphorylation of AMPK, suggesting that vinpocetine is a potential therapeutic agent in neuroinflammatory injury.